Socio-cultural Factors Influencing the Incidence of Stunting among Children Under Five in the Tengger Tribe, East Java, Indonesia - Annessa Marknalia Sasqia Putri; Argyo Demartoto; Bhisma Murti; Revi Gama Hatta Novika; Erindra Budi Cahyanto (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2026)
Background: Indications of stunting incidence in toddlers of the Tengger Tribe in East Java, related to socio-cultural practices in daily life that have an impact on health conditions and nutritional fulfillment of toddlers. This study aims to analyze the socio-cultural factors that affect the incidence of stunting in Tengger Tribe toddlers in East Java.Subjects and Method: This study is a qualitative research with a phenomenological approach. The research was conducted at the Lumajang Regency Health, Population Control, and Family Planning Office (P2KB), Senduro District Office, Senduro Health Center, and Ranupani Village. A total of 9 key informants, including the head of nutrition and public health, the head of population and family planning, the head of the Senduro Health Center, nutritionists, village midwives, family planning field officers of Senduro District, the head of the Ranupani Village government, the traditional shaman of the Tengger Tribe, and the baby shaman. A total of 9 mothers of toddlers as the main informants and 9 supporting informants were purposively sampling, including family members, cadres, health care officers, and sanitarians. Data collection was carried out through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model.Results: The study showed limited maternal knowledge about the health conditions and growth of toddlers. Traditional shamans play an important role in social decision-making, while gender equality affects the workload of mothers in economic activities. The parenting and care of toddlers is influenced by the cultural practices of the Tengger Tribe which are still strongly attached to daily life, as well as the environmental conditions of mountain communities who mostly depend on the agricultural sector for their livelihoods. Belief in ancestral spirits influences health decisions, through restrictions on maternal activity and mobility during pregnancy and after childbirth, as well as dietary restrictions that are believed to have adverse effects on pregnancy and toddlers.Conclusion: The incidence of stunting in toddlers of the Tengger Tribe is related to socio-cultural factors which include maternal knowledge, social interaction patterns, toddler parenting patterns, and belief in ancestral spirits in health decision-making.